TSG-6 inhibits osteoclast activity via an autocrine mechanism and is functionally synergistic with osteoprotegerin. - Mahoney, D; Swales, C; Athanasou, N; Bombardieri, M; Pitzalis, C; Kliskey, K; Sharif, M; Day, A; Milner, C; Sabokbar, A (2011)
TSG-6 (the product of tumor necrosis factor [TNF]-stimulated gene 6) has a potent inhibitory effect on RANKL-mediated bone erosion. The aim of this study was to compare the activity of TSG-6 with that of osteoprotegerin (OPG) and to investigate its role as an autocrine modulator of cytokine-mediated osteoclast formation/activation. We also determined TSG-6 expression in inflammatory joint disease.